The Impact of Caffeine and Coffee on Human Health - Cornelis, Marilyn (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
The purpose of this Special Issue is to provide a thorough and up-to-date presentation of research investigating the impact of coffee and/or caffeine intake on various health outcomes. Areas of interest include, but are not limited to, the following topics: Human clinical trials of coffee or caffeine use in relation to disease or intermediate phenotypes. Epidemiological studies of habitual coffee or caffeine intake in relation to human health, among the general public, as well as, among special populations (i.e., children, pregnant women, diabetics, cancer patients, hypertensives, etc.). Mechanisms of action of nutrients and other bioactive components of coffee/caffeine. Studies integrating genetic or physiological markers of coffee/caffeine intake to investigations of coffee and health.